1981
DOI: 10.1177/002221948101400713
|View full text |Cite
|
Sign up to set email alerts
|

Recategorization of WPPSI Scores for Kindergarten Children with Learning Difficulties

Abstract: Thirty kindergarten children with teacher-identified learning difficulties were matched for age, sex, and socioeconomic status with 30 children who were not experiencing any problems learning. All subjects were administered the Wechsler Preschool and Primary Scale of Intelligence (WPPSI). The scaled scores on the WPPSI were then recategorized according to Bannatyne's suggested regroupings to determine whether it was possible to identify potential learning difficulties on the basis of the pattern of these recat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Birch and Belmont, 1965) pointed to auditory sequential memory deficits as characterising children with learning problems, especially reading problems. Whatever the reasons for the Spatial \Conceptual\Sequential sequencing, these studies have traditionally been confined to elementary school populations tested with the WISC-R. Michayluk (1981) recategorized the WPPSI according to Bannatyne's (1974) model. The mean scaled scores on the subtests Block Design, Picture Completion, and Geometric Design were used to calculate the Spatial score.…”
mentioning
confidence: 99%
“…Birch and Belmont, 1965) pointed to auditory sequential memory deficits as characterising children with learning problems, especially reading problems. Whatever the reasons for the Spatial \Conceptual\Sequential sequencing, these studies have traditionally been confined to elementary school populations tested with the WISC-R. Michayluk (1981) recategorized the WPPSI according to Bannatyne's (1974) model. The mean scaled scores on the subtests Block Design, Picture Completion, and Geometric Design were used to calculate the Spatial score.…”
mentioning
confidence: 99%
“…Hagin, Silver, and Corwin (1971) studied 30 children for whom learning problems were predicted and found that their three WPPSI IQ Scores were significantly lower than those of the "normal group." Another popular area of research on the WPPSI has been the regrouping of subtests for clinical analysis (Badian, 1984; Michayluk, 1981; Reynolds & Gutkin, 1981). These researchers usually found that the WPPSI profile of normal learners and children with learning problems differs from the WISC-R pattern when using Bannatyne's (1974) approach.…”
mentioning
confidence: 99%